ROLE OF SOCIAL SUPPORT TOWARD STUDENT ACADEMIC SELF-EFFICACY IN ONLINE LEARNING DURING PANDEMIC - WAHYU SAEFUDIN; SRIWIYANTI SRIWIYANTI; SITI HAJAR MOHAMAD YUSOFF (Jurnal Tatsqif, 2021)
The Covid-19 pandemic has changed many government policies. One of them is distance learning policies implemented by affected countries. However, distance-learning or online learning program has received a negative response due to the lack of preparation and socialization. Therefore parents, teachers, and students find it difficult to adapt. Students feel doubtful and anxious about success in online learning programs. At the same time, students need high self-efficacy to advance in learning and get the desired results. Therefore, this study aims to describe the description of student self-efficacy in online learning during the pandemics. The research method used is a qualitative approach. The primary data in library studies are compiled through various search pages for scientific journals, books, and government regulations. The study results show that not all students' academic self-efficacy during distance learning is high. Some students are in the lower middle category. In addition, social support has a strong role in increasing students' academic self-efficacy. Thus, this research can be used as an evaluation material in education and a reference in creating policies.